PM2.5 exposure reprograms cell cycle dynamics in uterine immune cells at single-cell resolution - Zhang, Lin; Tian, Jiaqi; Zheng, Yongfei; Duan, Shuyin (Frontiers in Immunology, 2025)
BackgroundFine particulate matter (PM2.5) exposure has been associated with adverse effects on reproduction, yet the underlying cellular mechanisms remain poorly understood.MethodsUsing single-cell RNA sequencing, we systematically investigated cell cycle dynamics of immune cell populations in the mouse uterus following PM2.5 exposure. Analysis of 9,000 balanced cells was performed to identify distinct cell populations and characterize changes in cell cycle distribution and gene expression profiles.ResultsPM2.5 exposure induced distinct alterations in immune cell composition and cell cycle distributions. Notably, we observed significant changes in immune cell populations, including reductions in macrophages (510 to 58 cells), NK cells (445 to 91 cells), and granulocytes (1597 to 1 cells). Cell cycle analysis demonstrated cell type-specific responses to PM2.5 exposure: macrophages showed increased G1 phase representation (53.45%, +7.37%) with decreased G2M phase cells (18.97%, -12.79%), while NK cells exhibited relatively modest cell cycle alterations (G1: 28.6%, +2.5%; G2M: 45.1%, +2.6%; S: 26.4%, -5.1%). Differential gene expression analysis further identified crucial regulatory genes involved in cell cycle control, including Cd81 and Nrp1 in macrophages, Vps37b in NK cells. Integration of cell cycle markers with differentially expressed genes revealed distinctive phase-specific perturbations across immune cell types.ConclusionPM2.5 exposure induces cell type-specific alterations in cell cycle progression of uterine immune cells, which provides novel mechanistic insights into environmental pollution-induced reproductive dysfunction.